4
If the number (count) of odd values to sum is odd, then the answer is odd.If the number (count) of odd values to sum is even, then the answer is even.
If you mean: (x+3)^2 = (x+2)^2 +13 Then the value of the number x works out as 4
2(8 + 5) = 2(13) = 26
The number is 4 (4+3) * (4+3) = 49 (4+2) * (4+2) = 36 49 - 36 = 13
2n+13
2n+13
4
4
13 and 26
If the number (count) of odd values to sum is odd, then the answer is odd.If the number (count) of odd values to sum is even, then the answer is even.
[(x+3)^2] - [(x+2)^2] = 13 ==> 2x = 8 ==> x = 4. the number is 4!
If you mean: (x+3)^2 = (x+2)^2 +13 Then the value of the number x works out as 4
2(8 + 5) = 2(13) = 26
3 + 23 7 + 19 13 + 13
The number is 4 (4+3) * (4+3) = 49 (4+2) * (4+2) = 36 49 - 36 = 13
Count how many of the numbers are odd. If an odd number of them are odd, then their sum is odd. If an even number of them are odd, then their sum is even.